Homelessness at diagnosis is associated with death among people with HIV in a population-based study of a US city. (1st September 2019) - Spinelli, Matthew A.; Hessol, Nancy A.; Schwarcz, Sandy; Hsu, Ling; Parisi, Maree-Kay; Pipkin, Sharon; Scheer, Susan; Havlir, Diane; Buchbinder, Susan P.
Abstract : Objective: San Francisco, California, has experienced a 44% reduction in new HIV diagnoses since 2013 supported by its 'Getting to Zero' initiative; however, the age-adjusted mortality rate in people with HIV (PWH) has not decreased. We sought to identify factors associated with death among PWH in San Francisco. Design: Population-based incidence-density case–control study. Methods: Among PWH in the San Francisco HIV surveillance registry, a random sample of 48 decedents from 1 July 2016 to 31 May 2017 were each matched to two to three controls who were alive at the date of death (108 controls matched on age and time since diagnosis). Covariates included demographics, substance use, housing status, medical conditions, and care indicators from the study population. We used matched-pair conditional logistic regression to examine factors associated with mortality. Results: Of the 156 PWH in the study, 14% were African-American, 14% Latino, and 8% female sex. In adjusted analysis, factors associated with higher odds of death included: homelessness at HIV diagnosis [adjusted odds ratio (AOR) = 27.4; 95% confidence interval (CI) = 3.0–552.1], prior-year IDU (AOR = 10.2; 95% CI = 1.7–128.5), prior-year tobacco use (AOR = 7.2; 95% CI = 1.7–46.9), being off antiretroviral therapy at any point in the prior year (AOR = 6.8; 95% CI = 1.1–71.4), and being unpartnered vs. married/partnered (AOR = 4.7; 95% CI = 1.3–22.0). Conclusion: People homeless at HIV diagnosis had 27-fold higher odds of death compared with those with housing; substance use and retention on antiretroviral therapy in the prior year are other important intervenable factors. New strategies to address these barriers, and continued investment in supportive housing and substance use treatment, are needed.